TAG QUESTIONS: OLIVIA POPE'S WOMEN’S LANGUAGE DOMINANCE IN "SCANDAL" TV SHOW, SEASON 5 - Hardiyanti, Risma; Maharani Santika, I Dewa Ayu Devi (Linguistik : Jurnal Bahasa dan Sastra, 2023)
This research, titled Tag Questions: Olivia Pope's Linguistic Dominance in "Scandal" TV Show, Season 5, examined language features used mostly by women. The research sought to identify the tag question as one of the gender-specific linguistic elements utilized by Olivia Pope. This research focuses on Lakoff's (1975) idea of the linguistic characteristics of women. The formal and informal techniques are used to convey the analysis, which was conducted using qualitative methods based on Lakoff's (1975) theory about women's language. The data was gathered using the documentation method. The research revealed that the female main character employed one dominant kind of one of the 10 categories of women’s language traits. Because the female main character in this TV series season 5 was a typical independent woman who tended to turn a statement into a question to reduce the force of the statement, the results demonstrate that tag questions became the dominant type of women's language feature uttered in this TV series season 5.